2022
DOI: 10.18502/jmehm.v15i4.10190
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between ethical decision-making and professional behavior in Iranian nursing students

Abstract: Ethical decision-making and professional behavior are essential skills in nursing profession, hence educational programs should be designed to enable future nurses to tackle problems related to ethical decision-making. This descriptive, correlational and analytical study aimed at determining the ability of Iranian nursing students to make ethical decisions as well as relationship between such decisions and professional behavior. The present study used census to select 140 freshmen from the School o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In one study, Rajeswara et al (2016) showed that nursing students were unable to correctly apply their theoretical learnings in clinical practice, leading to low-quality clinical and professional performance (11). Thus, the existing gap in knowledge transfer from the theoretical classroom to clinical practice indicates the need to develop more effective teaching programs (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Rajeswara et al (2016) showed that nursing students were unable to correctly apply their theoretical learnings in clinical practice, leading to low-quality clinical and professional performance (11). Thus, the existing gap in knowledge transfer from the theoretical classroom to clinical practice indicates the need to develop more effective teaching programs (12,13).…”
Section: Introductionmentioning
confidence: 99%